PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP KREATIVITAS BELAJAR SISWA PADA PELAJARAN PENDIDIKAN PANCASILA KELAS VI SDN 182 PEKANBARU - Ulfa Nadiyah; Zaka Hadikusuma Ramadan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
In the learning process, teachers are able to encourage students to think creatively. The Mind Mapping learning model is one of the learning models that can make students learn creatively in producing ideas, and easily record the material that has been obtained. In the subject of Pancasila education in order to instill the values ​​contained in Pancasila. Students have difficulty in understanding and learning something Pancasila Education learning that has extensive material and requires memorization. The researcher took the initiative to apply the Mind Mapping learning model to Pancasila Education lessons to improve student creativity. In this study, the researcher used a quantitative research approach, the type of research chosen was Quasi Experimental Design. This design has two groups, namely the experimental group and the control group. The data collection technique used in this study was using a questionnaire and observation sheet. From the results of the research that has been conducted at SD Negeri 182 Pekanbaru, there is an Influence of the Mind Mapping Learning Model on Student Learning Creativity in Pancasila Education Learning Class VI at SDN 182 Pekanbaru. Based on the T Test with Independent Sample t-test on student learning creativity, it is known that the Sig. (2-tailed) value is 0.000. Based on the decision-making criteria, 0.000 < 0.05 then H0 is rejected and Ha is accepted. So it can be concluded that there is an influence of the use of the Mind Mapping Model on Student Learning Creativity in Pancasila Education Lessons for Class VI of SD Negeri 182 Pekanbaru.